Project management tools and techniques: A practical guide - Carstens, Deborah Sater; Richardson, Gary L. (London CRC Press, 2021)
The topic of project management is truly an evolution of art seeking science. This activity involves balancing project objectives against the constraints of time budget and quality. Achieving this balance requires skill experience along with the use of many tools and techniques which are the focus of this book. This new edition provides updated content to incorporate examples from Microsoft Project 2016 and material from the Project Management Body of Knowledge.